Spectroscopy theory in one dimension - Williams, Darren L.; Jackson, Victoria S. (AIP Publishing, 2022)
Spectroscopy Theory in One Dimension is an in-depth introduction to quantum chemistry using classical analytical calculus and symmetry group theory. The book employs the one-dimensional particle in a box and particle on a ring systems to develop the theoretical underpinnings of real-life spectroscopy and quantum mechanics. Wave functions, energy equations, transition intensities, and spectroscopic selection rules for absorption, emission, Rayleigh, and Raman spectra are derived and applied to explore why the sky is blue, why sunsets are red, and how quantum effects depend upon mass, size, temperature, and spectral resolution. Readers will understand to: Predict three-dimensional spectroscopic behavior using one-dimensional examples; Assign quantum transitions in real spectroscopic data using analytical calculus and group theory; Connect the mysterious quantum mechanical wave function to everyday experiences of light and color
Keywords: Spectrum analysis; Chemistry; Analytical chemistry; Chimie; Chimie analytique; chemistry; chemical analysis; SCIENCE / Physics/Optics & Light; SCIENCE / Chemistry/Analytic; SCIENCE / Physics/Quantum Theory